Technological and economic features of ethyl technical ethanol manufacture - Boiko, Petro (My University, 2019)
У статті розглядаються питання виробництва технічного етанолу із зерна з точки зору поєднання технологічних заходів та визначення економічної доцільності збуту продукції на різних ринках. Уточнюється, що специфікою такого впровадження є конкуренція технічного етанолу та продуктів нафто- і газоорганічного синтезу. Розглянуто ряд заходів, які при незначних величинах їх реалізації забезпечують зниження собівартості технічної переробки зерна на технічний етиловий спирт. The article deals with the issues of producing technical ethanol from the grain in terms of the combination of technological measures and the determination of the economic feasibility of marketing products in different markets. It is specified that the specifics of such implementation are competition of technical ethanol and products of oil and gas-organic synthesis. A number of measures are considered, which, at insignificant values of their implementation, provide a reduction in the cost of technical processing of grain into technical ethanol.
Keywords: technical ethanol; methanol; products of technical purpose; yeast; mash; beer; етанол технічний; метанол; продукти технічного призначення; дріжджі; бражка; пиво; кафедра біотехнології продуктів бродіння і виноробства